Strategi Peningkatan Pendapatan Pengrajin Pada Usaha Kerajinan Mendong Dan Rotan Di Desa Mujing Perspektif Ekonomi Islam - Ferry Febriansyah; Yunaita Rahmawati (Niqosiya: Journal of Economics and Business Research, 2024)
The Mujing Village craft business is one of the businesses operating in the creative industry in Nawangan District. A craft business is an organized business activity to produce craft products in order to make a profit and meet the needs of the craftsmen. In a business, strategic planning needs to be carried out so that the business runs well and produces income as expected. This research aims to determine the strategies for increasing craftsmen's income carried out by Mujing Village craft businesses. This type of research is field research, which collects data and information when the event occurs. The technique used by researchers is descriptive research using qualitative methods. Meanwhile, data collection techniques use interview and documentation methods. The results of the research show that 1) The strategy to increase the income of craftsmen in the Mujing Village craft business uses four indicators, namely by building quality human resources, qualified equipment, implementing good management, fairness and equality. 2) The advantages and disadvantages of implementing this strategy are the advantages such as increasing production efficiency, product competitiveness, as well as labor coordination and productivity. However, there are disadvantages such as high costs and difficulties in implementing the plan. 3) The impact of implementing this strategy is to directly increase income, improve employee welfare and encourage growth. Through implementing this strategy, the income of craftsmen in the Mujing Village craft business has increased substantially.